Efektifitas Lotion Anti Nyamuk Ekstrak Etanol Daun Kenikir (Cosmos caudatus) - Suprianto; Hendri Faisal; Endang Subekti (Yayasan Penelitian dan Inovasi Sumatera, 2021)
Mosquitoes are one of those insects with an often annoying presence. Saponins, polyphenols, and essential oils are found in the Kenikir plant (Cosmos caudatus). Experimental research was conducted with tests covering: organoleptic, homogeneity, pH, and effectiveness. Organoleptic lotions at concentrations of 5%, 10% and 15% have a dark green colour with a distinctive odour of Kenikir. Lotions with a concentration of 5% are homogeneous, while at concentrations of 10% and 15% are not homogeneous. Organolepticrequirements and homogeneity as lotions are met. The results obtained showed that the Kenikir leaf extract was effective at repelling mosquitoes.